Detection of muramic acid in a carbohydrate fraction of human spleen. - Hoijer, M A (1995)
In previous studies, we showed that peptidoglycan polysaccharides from anaerobic bacteria normally present in the human gut induced severe chronic joint inflammation in rats. Our hypothesis is that peptidoglycan from the gut flora is involved in perpetuation of idiopathic inflammation. However, in the literature, the presence of peptidoglycan or subunits like muramyl peptides in blood or tissues is still a matter of debate. We were able to stain red pulp macrophages in all six available human spleens by immunohistochemical techniques using a monoclonal antibody against gut flora-derived antigens. Therefore, these human spleens were extracted, and after removal of most of the protein, the carbohydrate fraction was investigated for the presence of muramic acid, an amino sugar characteristic for peptidoglycan. Using three different methods for detection of muramic acid, we found a mean of 3.3 mumol of muramic acid with high-pressure liquid chromatography, 1.9 mumol with a colorimetric method for detection of lactate, and 0.8 mumol with an enzymatic method for detection of D-lactate per spleen (D-lactate is a specific group of the muramic acid molecule). It is concluded that peptidoglycan is present in human spleen not as small muramyl peptides as were previously searched for by other investigators but as larger macromolecules probably stored in spleen macrophages.